The Sense of Love and Heartbreak in Tyler, the Creator’s Album “Igor”: Figurative Language Analysis - Mahasari, Mirah; Rahayuni, Ni Ketut Sri (International Journal of Linguistics and Discourse Analytics, 2025)
This study explored how figurative language was used to convey emotions of love and heartbreak in the song lyrics of IGOR, an album by Tyler, the Creator. As a contemporary artist known for emotional depth and creative expression, Tyler’s work provided rich material for literary analysis. A qualitative descriptive method was employed, applying Kennedy and Gioia’s (1995) theory to identify figurative language and Leech’s (1981) framework to analyze types of meaning. Data were collected through documentation of official song lyrics and textual analysis, which involved close reading, identification of figurative expressions, and interpretation of their underlying meanings. The findings showed that Tyler frequently employed metaphors, personification, and hyperbole, which intensified the portrayal of emotional struggles and deepened the listener’s engagement with the themes of longing, love, and heartbreak. The analysis also revealed the presence of connotative, affective, and reflected meanings that enriched the emotional resonance of the songs. In conclusion, this study demonstrated the literary value of song lyrics and affirmed the relevance of applying literary theories to music as a form of modern literature.